Determinants of indebtedness: Influence of behavioral and demographic factors - Mahfuzur Rahman; Nurul Akidah Azmaya Lim; Md. Abdul Kaium Masud; Yusof Ismail (International Journal of Financial Studies, 2020)
This study aims to examine the influence of behavioral and demographic factors on indebtedness by constructing a model using specific determinants. The exploratory method is used through the partial least square (SmartPLS) technique, by surveying 320 respondents in Kuala Lumpur, Malaysia. A self-administered questionnaire was administered to respondents, addressing both demographic and behavioral factors. The results confirmed four of the eight hypotheses stated. Among the determinants, risk perception had a highly significant relationship with both materialism and emotion, while indebtedness had a relationship with emotion and materialism. The findings also indicated that significant differences exist between indebtedness and behavioral factors on the basis of gender, marital status, age, income, and dependence on credit cards and loans. The results may assist various economic players to design better models for credit offerings and address the credit problem in the long term.
Keywords: G32; G11; M30; 330; behavioral factors; demographic factors; indebtedness; Malaysia